Stigma scale of epilepsy: the perception of epilepsy stigma in different cities in Brazil Percepção do estigma na epilepsia em diferentes cidades do Brasil - Paula T. Fernandes; Ana Lúcia A. Noronha; Josemir W. Sander; Li M. Li (Arquivos de Neuro-Psiquiatria)
PURPOSE: To assess the perception of epilepsy stigma in different regions of Brazil. METHOD: The Stigma Scale of Epilepsy (SSE) questionnaire was applied to people in different Brazilian urban settings. The survey was performed on individual basis; an interviewer read the questions to the subjects and wrote down the answers. The same procedure was applied to all the subjects and took around 10 minutes. RESULTS: 266 questionnaires were completed in four different towns of Brazil (Curitiba=83; São Paulo=47; Vila Velha=79; Ipatinga=57). The overall stigma score was 49.7 (median). Different scores were obtained in each locality. Vila Velha=42; Curitiba=49; São Paulo=52; Ipatinga=54 (ANOVA [2.262]=3.82; p=0.01). CONCLUSION: This study showed differences in the perception of stigma, which may depend on cultural and regional aspects. The concept of stigma has cultural perspectives, depending on the region and the context where each person lives. The understanding of this aspect of epilepsy is important to promote better de-stigmatization campaigns, considering the cultural and social differences. OBJETIVO: Identificar a percepção do estigma na epilepsia em diferentes regiões do Brasil. MÉTODO: A Escala de Estigma na Epilepsia foi aplicada em 266 pessoas de quatro diferentes cidades do Brasil (Curitiba, São Paulo, Vila Velha e Ipatinga). Em todas as situações, as pessoas foram entrevistadas individualmente, sendo que as questões eram lidas para os sujeitos. As condições de aplicação foram as mesmas nas cidades e a aplicação durou aproximadamente 10 minutos. RESULTADOS: Foram aplicados 266 questionários em três diferentes cidades do Brasil (Curitiba=83; São Paulo=47; Vila Velha=79; Ipatinga=57). A média do escore geral da EEE foi 49,7. Na avaliação das quatro cidades separadamente, houve diferença significativa entre elas: Vila Velha=42; Curitiba=49; São Paulo=52 e Ipatinga=54 (ANOVA [2,262]=3,82; p=0,01). CONCLUSÃO: Este estudo mostrou diferenças na percepção do estigma, de acordo com as diferenças culturais e regionais. Neste contexto, podemos falar de uma perspectiva cultural para o conceito de estigma, sendo influenciado pela região e pelo contexto no qual a pessoa está inserida. O entendimento deste processo do estigma é importante para se propor campanhas efetivas de intervenção no estigma da epilepsia, considerando as diferenças sociais e culturais.